The Potential of Restaurant Taxes to Increase Sumenep Regency's Original Revenue in 2019-2022 - Wahyu Rochana; Totok Mardianto (Institute of Computer Science (IOCS), 2020)
The Study on the Potential of Restaurant Taxes for Increasing Local Revenue in Sumenep Regency 2019-2022, aims to find out the potential for Restaurant Tax and make an estimate of the potential growth of Restaurant Tax to increase Local Revenue in SUMENEP Regency from 2019 to 2022. The Specific targets to be achieved in this research are: 1. It is necessary to analyze the potential of local taxes to increase local revenue for the next 4 years in Sumenep Regency. 2. The need to optimize the potential Restaurant Tax to Increase Local Revenue for the next 4 years in Sumenep Regency. The method is carried out on the basis of documentary research and direct observation carried out on the research object, with several stages, as follows: The first stage is to analyze the growth rates of each type of local tax and developments during the 2015-2018 period. The second stage is to analyze the growth rate of restaurant tax types and developments during the 2015-2018 period. The third stage of this research activity is to analyze the contribution of each type of local tax that will have an effect on the total local tax revenue. The Fourth stage is to analyze the restaurant tax contribution. The fifth stage is to makae projections. potential of Sumenep Regency Restaurant Tax during the 2019-2022 period. The analysis of the results of the Study on the Potential of Restaurant Taxes to increase Local Revenue of Sumenep Regency generally, as follows: Hotel tax growth rate is the biggest one (86.07%), the second biggest is restaurant tax (45.33%) and the smallest is Land and Building Tax. The second analysis is the growth rate of restaurant tax from 2014 to 2018 has fluctuated where the highest growth occurred in 2015, which was 78.91%, then the lowest growth in restaurant tax was 21.39% which occurred in 2016. The contribution of restaurant taxes to regional taxes and local revenue of Sumenep Regency from 2014 to 2018 has fluctuated where the largest contribution occurred in 2017, 19.22%. Analysis of the condition of the average types of taxes based on overlay analysis (growth and contribution to PAD), during the past 5 years are: There are 3 types of taxes in the prime classification, namely Hotel Tax, Restaurant Tax, Street Lighting Tax. There are 3 types of tax with the Developing classification, namely BPHTB tax, mineral tax and advertisement tax.